Screening of factors for biodelignification of oil palm trunk using pleurotus ostreatus - Mohd Rasidi, Rasol (2012)
Delignification of lignocellulosic material is a crucial part in most research where it needs to be done to ensure the lignin compound are removed from the hemicelluloses and celluloses contained in the material.Unbound hemicelluloses and celluloses can be used further in application such as production of bioethanol.Currently known delignification method includes physical,chemical,and biological method.The biological method or biodelignification is known as a method that uses less energy and consume fewer chemicals that lead it to become the only method with environmental and cost friendly approach. Therefore, this research are conducted to study the factors that affect the biodelignification of oil palm trunk and to screen the factor that has significant effect on biodelignification of oil palm trunk using Pleurotus ostreatus. The effect of temperature,pH, humidity,light exposure,moisture content,fungi to medium ratio,and contact time on biodelignification process of oil palm trunk will be studied in this research.The oil palm trunk was incubated with the Pleurotus ostreatus in a temperature controlled incubator for a predetermined period of time.It was later cleaned after the incubation period ends and dried.The dried oil palm trunk was then analysed using the Klason-Lignin determination method where the lignin percentage in the oil palm trunk sample was obtained. The analysis done using Two-Level Factorial by Design Expert software shows that four factors are affecting with high contribution towards the biodelignification.The factors are the temperature, pH, fungi to medium ratio,and moisture content.The factors of temperature,pH,fungi to medium ratio, and moisture content contribute with 32.2%, 10.08%, 8.82% and 7.63% of contribution respectively to the biodelignification process.Besides the factor,interaction between factors also contributes to the biodelignification itself.The interaction between temperature and pH and also interaction between temperature and fungi to medium ratio gives contribution to biodelignification process with 18.29% and 8.82% respectively.The factor that found to have significant effect on biodelignification of oil palm trunk using Pleurotus ostreatus is temperature,pH,fungi to medium ratio,and moisture content and is suitable to be the factor for optimization experiment.